2015
DOI: 10.17235/reed.2015.3979/2015
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome subtypes: Clinical and psychological features, body mass index and comorbidities

Abstract: Background: Irritable bowel syndrome (IBS) is classified into subtypes according to bowel habit.Objective: To investigate whether there are differences in clinical features, comorbidities, anxiety, depression and body mass index (BMI) among IBS subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
4
31
0
4
Order By: Relevance
“…However, based on clinical experience, patients with IBS-M are more difficult to treat. Other published studies also supported clinical difference in the various IBS-subtypes, with patients with IBS-M subtype posing more difficulties in the management[64-66]. Hence, there is a good chance that the difference observed would be valid.…”
Section: Discussionmentioning
confidence: 76%
“…However, based on clinical experience, patients with IBS-M are more difficult to treat. Other published studies also supported clinical difference in the various IBS-subtypes, with patients with IBS-M subtype posing more difficulties in the management[64-66]. Hence, there is a good chance that the difference observed would be valid.…”
Section: Discussionmentioning
confidence: 76%
“…Trauma and anxiety-related disorders are major health burdens worldwide, with increased incidence in women relative to men (Altemus et al, 2014). Associated symptoms are highly prevalent in patients with dysbiosis-related syndromes like IBS, which also disproportionately affect women (Kibune-Nagasako et al, 2016;Lovell & Ford, 2012). Our data add to growing evidence for a role of gut microbiota in the pathophysiology of psychiatric conditions (Cowan et al, 2018;Cryan & Dinan, 2012;Kelly et al, 2016;Malan-Muller et al, 2018;MacQueen, Surette, & Moayyedi, 2017), and highlight the need to consider sex as a biological variable (Shansky & Woolley, 2016).…”
Section: Discussionmentioning
confidence: 53%
“…Sex differences in aversive conditioning (Asok, Kandel, & Rayman, 2019;Blume et al, 2017) and gut microbiome structure (Jašarević, Morrison, & Bale, 2016;Markle et al, 2013) have also been reported, albeit inconsistently (Ding & Schloss, 2014;Org et al, 2016). Furthermore, functional bowel disorders like IBS, the most common form, disproportionately affect women (Kibune-Nagasako, García-Montes, Silva-Lorena, & Aparecida-Mesquita, 2016;Lovell & Ford, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We chose the above covariates because they may be associated with dietary restrictions and gastrointestinal symptoms like irritable bowel syndrome. [9][10][11][12] All tests were two-tailed with a significance level set at p<0.05. The data were analysed with STATA V.12.…”
Section: Methodsmentioning
confidence: 99%